Plant-Human Futurisms in the Australian Tropics: Native Grasses and the Carbon_Dating Art Project - Tania Leimbach; Keith Armstrong; Jane Palmer; Delissa Walker Ngadijina; Gerry Turpin (eTropic: electronic journal of studies in the tropics)
The tropics have been first to suffer from the effects of unsustainable practices on land and sea. The Carbon_Dating project (2019 to 2025)—an artwork and cultural campaign designed to provoke a re-imagining of human-grass futures that builds relationships with native grasses—has worked in Far North Queensland, Australia, with two First Nations participants: Mbabaram Elder, knowledge-holder, and ethnobotanist Gerry Turpin, and Kuku Yalanji Master Weaver and artist Delissa Walker Ngadijina. Using traditional knowledge and creative works to forge new imaginaries that selectively choose or refuse those of the coloniser, the contributions of these two participants are an assertion of Indigenous relationalities in the tropics, and offer others a way of re-imagining plant-human futures in the wider world.